Frequency of Text Neck Syndrome in Medical Students due to Excessive Usage of Electronic Devices (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine the frequency of text neck syndrome in medical undergraduate students using smart phone, tablets or laptop.Methods: It was a cross-sectional survey using non-probability convenient sampling technique at Combined Military Hospital(CMH) Lahore medical college and Institute of dentistry, Lahore from January 2019 to February 2019 in a period of one month. Our sample size was 500 undergraduate students from first year till final year MBBS and BDS. The inclusion criteria of the study were all medical undergraduates who were using smart phone, tablet and laptop for past six-month or more. We filled all questionnaire at the spot. The exclusion criteria of the study were all questionnaire which were filled with the help of colleague, going through internet, and left incomplete. Data was obtained using pre-tested self-administered questionnaire.Results: Out of total 500 medical students, 292 (58.4%) were female and 208 (41.6%) were male. The mean age of our study subjects were 23 ±2 years. The frequency of text neck syndrome was documented in 218 (43.6%) students. There was no disability (0-4 scores) in 292(58.4%) students, mild disability(5-14 score) in 150(30%) students and moderate disability (15-24 scores) in 58 (11.6%) with p-value